The Influence of Leadership and Competence on the Performance of Educational Personnel at PTIQ University with Job Satisfaction as a Mediating Variable - Haryoto, Cecep; Hotimah, Husnul; Prayitno, Irwan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to examine and analyze the impact of Leadership and Competency on the Performance of Educational Personnel, with Job Satisfaction serving as a Mediating Variable at PTIQ University. The independent variables considered are Leadership and Competency, while the dependent variables encompass the Performance of Educational Personnel, with Job Satisfaction acting as a mediating factor. Data collection involved distributing questionnaires to 160 respondents from the educational personnel of PTIQ University. Employing an associative quantitative approach, this research utilized primary data and applied Structural Equation Modeling (SEM) via Smart PLS. The findings reveal that Leadership exhibits a positive and significant influence on the Performance of Educational Personnel, indicating a coefficient value of 0.761. Likewise, Competency demonstrates a positive and significant impact on the Performance of Educational Personnel, with a coefficient value of 0.206. Furthermore, Leadership is found to affect Job Satisfaction positively and significantly, displaying a coefficient value of 0.605, while Competence also exhibits a positive and significant effect on Job Satisfaction, with a coefficient value of 0.249. Moreover, Leadership and Competency both positively and significantly affect the Performance of Educational Personnel through Job Satisfaction, with coefficient values of 0.512 and 0.217, respectively. Lastly, Job Satisfaction significantly influences the Performance of Educational Personnel, with a coefficient value of 0.278.